2014
DOI: 10.1007/s40264-014-0150-2
|View full text |Cite|
|
Sign up to set email alerts
|

The Weber Effect and the United States Food and Drug Administration’s Adverse Event Reporting System (FAERS): Analysis of Sixty-Two Drugs Approved from 2006 to 2010

Abstract: BackgroundThe United States Food and Drug Administration’s (FDA) Adverse Event Reporting System (FAERS) consists of adverse event (AE) reports linked to approved drugs. The database is widely used to support post-marketing safety surveillance programs. Sometimes cited as a limitation to the usefulness of FAERS, however, is the ‘Weber effect,’ which is often summarized by stating that AE reporting peaks at the end of the second year after a regulatory authority approves a drug. Weber described this effect in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 39 publications
(27 reference statements)
2
89
0
Order By: Relevance
“…Similar works for comparing multiple drugs are based solely on the counts of events for each drug or only one specific AE such as bleeding, while our work is designed for all the AEs combined and specifically for the FAERS data. [16,17]…”
Section: Discussionmentioning
confidence: 99%
“…Similar works for comparing multiple drugs are based solely on the counts of events for each drug or only one specific AE such as bleeding, while our work is designed for all the AEs combined and specifically for the FAERS data. [16,17]…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, SRS is a passive reporting system, and is, therefore, subject to many biases, such as under-reporting and overreporting [14]. In addition, SRS is subjected to the "Weber effect," which refers to an increase in adverse event reporting over the initial 2 years after a drug is approved, followed by a rapid decline in reporting rates [15]. However, no such effect was evident in our database; the number of reports of total hemorrhage due to prasugrel in JADER was 130 (2014 Q2-2016 Q1) and 173 (2016 Q2-2017 Q2) and that in FAERS was 227 (the fourth quarter [Q4] of 2009 -the third quarter [Q3] of 2011) and 305 (2011 Q4-2013 Q3).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the effect of underreporting of ADRs, we considered time after market approval of a NSAID in the analyses. Even though the Weber effect is described as ADR reports that peak at the second year after drug approval, other studies showed that ADR reports still increase up to 5 years . We calculated RORs in three strata of 5 years after market approval to ensure that time after market approval did indeed contribute to ROR differences.…”
Section: Methodsmentioning
confidence: 99%